How do minimally invasive versus open surgical approaches compare in terms of patient recovery for bladder stone management? : A Systematic Review - Teuku Muhammad Ramzi Akbar; Munawwir (The International Journal of Medical Science and Health Research, 2025)
Introduction : This systematic review investigates patient recovery outcomes between minimally invasive and open surgical approaches for bladder stone management. Bladder stones are a significant urological problem, often linked to bladder outlet obstruction and chronic urinary tract infections. While open cystolithotomy was historically the standard , minimally invasive techniques like percutaneous cystolithotripsy (PCCL), transurethral cystolitholapaxy (TUCL), and laparoscopic methods have emerged, aiming to improve patient outcomes and reduce morbidity. The choice of surgical method is complex, influenced by stone size, number, and patient-specific factors. This review aims to provide an evidence-based comparison to guide clinical practice. Methods : Following PRISMA 2020 guidelines , a systematic search was conducted across databases including PubMed, Semantic Scholar, Springer, Google Scholar, and Cochrane. Studies focusing on adult patients with bladder stones, comparing minimally invasive and open surgical approaches, and reporting recovery outcomes such as hospital stay, operative time, and complications were included. Data extraction was performed by a large language model , and a total of 14 studies met the inclusion criteria. Results : The results consistently show that minimally invasive approaches offer superior recovery outcomes. Operative times were significantly shorter for MIS, with PCCL being markedly faster than open vesicolithotomy (e.g., 38.20 minutes vs. 71.16 minutes). Hospital stays were also considerably reduced for MIS patients, often by one or more days. Postoperative catheterization time was notably diminished in MIS, for instance, 2.5 days for mini-PCCL versus 8.6 days for open surgery. While both approaches achieved high stone-free rates , complication rates were generally lower in MIS groups. However, specific MIS techniques carried distinct risks, such as higher urethral stricture rates with TUCL. Patient-reported outcomes like quality of life were infrequently assessed but indicated better outcomes with MIS. Conclusion : The aggregated evidence strongly supports minimally invasive surgery as the preferred approach for bladder stone management due to shorter operative times, reduced hospital stays, and lower morbidity. The optimal technique depends on stone characteristics and patient factors. Despite robust findings, further research is needed, particularly high-quality, multi-center randomized controlled trials focusing on standardized patient-reported outcomes and long-term complications. This will further refine clinical guidelines and enhance informed patient consent.